2018
DOI: 10.1186/s12889-018-5981-9
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of postpartum contraceptive utilization and associated factors among women of child bearing age in Aroressa District, Southern Ethiopia: a community based cross-sectional study

Abstract: BackgroundGlobally, more than 90% of women during the first year of postpartum period want to either delay or avoid future pregnancies. The first year postpartum period is more crucial time to use modern contraceptives that enhance maternal and child health, so more attention should be given on time of initiating modern contraceptive utilization after delivery. Therefore, the aim of this study was to assess the magnitude and associated factors of timely initiation of postpartum contraceptive utilization among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
44
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 17 publications
13
44
3
Order By: Relevance
“…These studies showed a dose-response type of relationship between antenatal care and postpartum contraception adoption; that is the likelihood of using postpartum contraception increased when women had frequent antenatal contacts. Our result also demonstrated a significant association between postpartum contraceptive use and early postnatal care, which is in agreement with other studies [20,27].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These studies showed a dose-response type of relationship between antenatal care and postpartum contraception adoption; that is the likelihood of using postpartum contraception increased when women had frequent antenatal contacts. Our result also demonstrated a significant association between postpartum contraceptive use and early postnatal care, which is in agreement with other studies [20,27].…”
Section: Discussionsupporting
confidence: 94%
“…The finding is comparable with the finding of the study done in Debre Tabor town, Northwest Ethiopia 63.0% (95% CI: 59%; 67.4%) [26]. This result was, however, higher than the 31.7% prevalence in Southern Ethiopia [20], 45.4% in western Ethiopia [27], and 29.3% in Northern Ethiopia [19], and lower when compared to the studies done in Hosana town (72.9%), Addis Ababa, Ethiopia (80.3%), and 86.3% of Kenya [28][29][30]. The low level of contraceptive use found in this study might reflect the over-reliance of lactating women on breastfeeding and menstruation status.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations